Dermatology Life Quality Index (DLQI) Score in Acne Vulgaris after Epigallocatechin-3-Gallate (EGCG) 3% as an Adjuvant of Tretinoin 0,025% Cream - Fajrin, Farah Meriana; Citrashanty, Irmadita; Listiawan, Muhammad Yulianto; Rahmadewi, Rahmadewi; Utomo, Budi; Murtiastutik, Dwi; Prakoeswa, Cita Rosita Sigit (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2023)
Background: Acne vulgaris (AV) often occurs at the age of puberty, most people with AV feel ashamed of their appearance. It has been believed that green tea contains high level antioxidant, such as Epigallocatechin-3-gallate (EGCG). Purpose: This study is to compare quality of life from the patient of acne vulgaris before and after using 3% Epigallocatechin-3-Gallate (EGCG) cream as adjuvant therapy of 0,025% tretinoin cream with 0,025% tretinoin cream alone in the treatment of AV. Methods: This study is a quasi-experimental study with a pre-test and post-test design, and a control group design aiming to know the difference in quality of life of 46 samples after administration of EGCG cream combined with tretinoin cream compared to the group that was given tretinoin cream alone in patients with AV for 12 weeks, and then evaluate patients satisfaction and change in quality of life after treatment using the Dermatology Life Quality Index (DLQI). Result: Statistical analysis found that there was a significant difference (p-value <0.05) in the quality-of-life value of research subjects in the treatment group when compared between the initial arrival to week 12 with a p-value of 0.000. Distribution of DLQI values in research subjects who were given 3% EGCG cream therapy as adjuvant therapy with 0.025% tretinoin cream. Conclusion: Both groups showed an improvement in the DLQI value with the interpretation of the DLQI value at week 12 being both 100%, but the treatment groups DLQI decline faster than the control groups.